Evaluating market prospects for Prekmurje dry ham in relation to consumption characteristics of dry meat products in Slovenia - Candek-Potokar M.; Arh M. (5. International Symposium on the Mediterranean Pig, 2007)
Prekmurje dry ham, or Prekmurska s?unka in Slovenian, is a traditional dry ham of the northeastern part of Slovenia. It is slightly smoked, can be dry or wet salted, with a typical pear-like form (prior to the curing process, the ham is de-boned, but left covered with subcutaneous fat and skin on the side). Prekmurje dry ham is protected by a geographical designation. Presently, it can only be found on the local market. Some producers wish to increase the production and enlarge their market. Therefore a study was set up to evaluate market opportunities of Prekmurje dry ham in view of consumption characteristics and perception of traditional dry-cured meat products as expressed by Slovenian consumers. Within the study, two focus group discussions with eight consumers per group and a telephone survey on 504 consumers were performed. The results obtained are presented; (i) consumers' perception of factors important for consumption and purchase of dry meat products; (ii) consumption characteristics of dry meat products; and (iii) consumers' perception of traditional dry meat products and particularly of Prekmurje dry ham. According to the results, dry-cured ham of Prekmurje has the extrinsic indicators which correspond to the image of value added product (origin, region, tradition). However, considering the whole Slovenian territory, telephone surveys demonstrated poor image of Prekmurje dry ham compared to other traditional products. Besides, in a blind sensory test of three dry hams which was made during focus group discussions, Prekmurje dry ham was the least appreciated among the participants. These results can be considered as unfavorable for a product which has yet to convince the consumers. Moreover, it seems that the poor image could be related to the lack of knowledge about the product which indicates a strong need for promotional activities, if producers wish to go beyond the regional market.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)